2021
DOI: 10.1515/eng-2021-0028
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Innovative Reliable Criteria Governing the Selection of Infrastructures Construction Project Delivery Systems

Abstract: No doubt that the most vital issues to achieve a great success project are the choice of best suitable project delivery methods. According to the experience of project management staff, the delivery of the project is chosen. However, that leads to similar repetitive issues, for example, exceeding the cost of the project and exceeding the project's schedule, and that's what many projects face. It is difficult to develop the management of the recurring issues of the project because there is no awareness of deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Unfortunately, the matching degree between project characteristics and the EPC model does not significantly affect owners' perceived usefulness of the EPC model, nor does it significantly affect the adoption behavior of the EPC model. This suggests that although previous studies have shown that the matching degree between project characteristics and the EPC model is an influential factor in the EPC model-adoption behavior [57], its impact on the EPC-adoption behavior is low compared with other factors. The possible reason is that China is currently in the early stage of promoting the EPC model, and whether public project owners adopt the EPC model is influenced more by policies and owner characteristics than by project characteristics.…”
Section: Key Findingsmentioning
confidence: 82%
“…Unfortunately, the matching degree between project characteristics and the EPC model does not significantly affect owners' perceived usefulness of the EPC model, nor does it significantly affect the adoption behavior of the EPC model. This suggests that although previous studies have shown that the matching degree between project characteristics and the EPC model is an influential factor in the EPC model-adoption behavior [57], its impact on the EPC-adoption behavior is low compared with other factors. The possible reason is that China is currently in the early stage of promoting the EPC model, and whether public project owners adopt the EPC model is influenced more by policies and owner characteristics than by project characteristics.…”
Section: Key Findingsmentioning
confidence: 82%
“…Selection of the contractor depends on qualifications or best value which is a procurement strategy that considers a combination of factors, including cost, qualifications, expertise, and reputation, to select a contractor or service provider that offers the most advantageous overall value for a project. The range of APDMs comprises methods like Design-Build (DB), Construction Manager at Risk (CMAR), Integrated Project Delivery (IPD), and many others [21,22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these methodologies, the traditional Design-Bid-Build (DBB) framework [19], Design-Build (DB) which integrates design and construction to overcome some of the hurdles [20] and one of the alternative delivery methods that is rapidly growing in popularity Construction Manager at Risk (CMAR) [21] will be focused. Additionally, as traditional project delivery systems used in the general construction sectors have many constraints [22], Integrated Project Delivery (IPD) which is an integrated delivery approach to the planning, design, and construction of civil engineering projects [23] and "an approach to enhance project implementation" [24], along with other innovative approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Simo's procedure Simo's procedure was used in several studies to obtain the weights of multiple factors based on the opinions of experts. This method can be applied based on a card playing procedure wherein different factors are classified into different clusters, which are ranked and weighted (Meshref et al, 2021). Experts evaluated each cluster: project data and organizational data.…”
Section: Construction Project Using Doementioning
confidence: 99%